O papel do crédito no desenvolvimento das cooperativas agropecuárias - Padilha, Wilian (2014)
In the 2000s, the Brazilian agricultural cooperatives experienced a process of horizontal and vertical expansion, which guaranteed highlight for the sector in national economic scenario. This growth occurred at different scales, in national, state and regional level. Thus, this dissertation seeks to analyze this process of growth in the recent period, with emphasis on the development of agricultural cooperatives in the Southwest of Paraná. The hypothesis of the research is that among the factors that conditioned such performance, federal policies for rural and agribusiness credit, were central to productive restructuring of cooperatives, which ensured the growth of the sector after 2003, moment of change important political and economic conditions in the country. The official credit in the period of modernization of agriculture, was the principal agent of development of cooperatives, and its scarcity in the nineties, has made the sector faced a time of recession, watching the rest of the national economy. In more recent context, funding policies regained its importance in the government plan, with increased resources and creation of sectorial and regional development programs. In the case of Southwest, the credit allowed for investment by cooperatives, especially an increase in production capacity, storage, productivity and agroindustrial integration.